فاعلية استخدام استراتيجية 2 + 2 للتدريس المصغر وعلاقتها بإكساب بعض مهارات التدريس لطلاب دبلوم التربية العام بكلية التربية جامعة جازان - أحمد، أسامة نبيل محمد; آدم، بشرى الفاضل إبراهيم; المالحي، هاني محمد حامد (جامعة طنطا - كلية التربية, 2018)
هدفت هذه الدراسة إلى التعرف على مدى فاعلية استخدام استراتيجية (2+2) للتدريس المصغر وعلاقتها بإكساب بعض مهارات التدريس لطلاب دبلوم التربية العام بكلية التربية جامعة جازان. تكونت عينه البحث من ٤٦ طالبا قسموا على مجموعتين تجريدية وضابطة بكل مجموعة عدد ٢٣ طالبا. استخدم الباحثون المنهج شبه التجريبي والملاحظة أداة لبحثه مستوى أداء الطلاب لمهارات التدريس الثلاث التخطيط والتنفيذ والتقويم. أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية بين متوسط أداء طلاب دبلوم التربية العام لصالح الذين استخدموا استراتيجية (2+2) للتدريس المصغر، مقارنة بالطلاب الذين يستخدمون الطريقة التقليدية، لا يوجد فروق ذات دلالة إحصائية بين متوسط الأداء في مهارات مرحلة التخطيط لطلاب دبلوم التربية العام عند استخدام استراتيجية (2+2) للتدريس المصغر، مقارنة بالطلاب الذين يستخدمون الطريقة التقليدية، وجود فروق ذات دلالة إحصائية بين متوسط الأداء في مهارات مرحلة التنفيذ والتقويم لصالح طلاب دبلوم التربية العام الذين استخدموا استراتيجية (2+2) للتدريس المصغر، مقارنة بالطلاب الذين يستخدمون الطريقة التقليدية، توجد فوائد أكتسبها الطالب/المعلم عند استخدام استراتيجية (2+2) في التدريس المصغر مثل إزالة الخوف والارتباك أمام الطلاب، وتبعث الثقة في نفوسهم، وتمكنهم من الشرح بطريقة سليمة، تجعل. الطالب يتعامل مع السبورة بصورة جيدة.
The aim of this study was to identify the effectiveness of the use of the strategy (2 + 2) for mini-teaching and its relation to imparting some teaching skills to students of general education diploma at the Faculty of Education, Jazan University. The research consisted of 46 students divided into two experimental groups and each group of 23 students. The researchers used the semi-experimental and observational approach as a tool to examine students' performance level of the three teaching- skills of planning, implementation and evaluation. The results of the study showed statistically significant differences between the average performance of students of the general education diploma for those who used the strategy (2 + 2) for the microteaching, compared to the students who use the traditional method, there are no statistically significant differences between the average performance in the skills of the planning stage for students of education diploma In comparison to students using the traditional method, there are statistically significant differences between the average performance in the implementation and evaluation skills for the general education diploma students who used the 2 + 2 strategy for microteaching who use the traditional method, there are the benefits gained by the student / teacher when using the strategy (2+2) in microteaching, such as removing the fear and confusion in front of the students, and inspire confidence in them, and enable them to explain properly, make the student deals with the board well.
Keywords: جامعة جازان -- إعداد المعلمين -- طرق التدريس -- مهارات التدريس -- التدريس المصغر